(untitled) (Research, Society and Development, 2022)
The challenges experienced by nursing residents in the face of total pain in cancer palliative care point to the need for training in the training of these professionals. The objective of this work is to discuss about the phenomenological perception of nursing residents about total pain in patients undergoing palliative cancer care. This is an integrative literature review including articles indexed in the Virtual Health Library (VHL) and CAPS Periodicals Platform. Data were collected between August 2021 to January 2022, in the MEDLINE, IBECS, LILACS, BINACIS, LIS, Web of Science, Embase and SCOPUS databases, following the PRISMA tool. As a result the total number of productions found using the Boolean operators was 2,441 articles, with 183 productions being selected. The final sample consisted of 32 articles for full reading, 10 articles were selected, totaling 10 articles. After analysis, it was observed that the publications involved related aspects, being categorized 03 main themes: "Perception of nursing residents about total pain in palliative cancer care", "Perception of good practices in nursing care about total pain in palliative care" and “Perception of professional training of nursing residents about total pain in palliative cancer care”. A large gap in the topic addressed was identified. All these aspects directly impact the performance of nursing residents in approaching total pain in palliative cancer care due to subjectivity and unpreparedness, making it necessary to address the issue in the training of these professionals.